Synonimy według Klementyny z Tańskich Hoffmanowej - Kozaryn, Dorota (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
The paper deals with the way of describing by Klementyna Hoffman (née Tańska), living 1798-1845, who is known in the history of literature as an author of children’s and women’s texts and a defender of national identity, the lexemes being regarded as synonyms by her. The presented analyses show that Tańska regarded as synonyms not only lexemes in the modern linguistic sense, and described not only lexemes but also concepts. The construction of particular descriptions was characteristic of Hoffman and had a lot of features in common with the 19th-century attempts of the Polish synonymists. This is demonstrated by a comparison of the way of describing synonyms by Klementyna Hoffman and Bp. Adam S. Krasiński. This that distinguished the activity of Tańska in this respect was the use of moralistic admonishments.